Evaluation of multidrug resistance in the Gram-negative microbiome of cancer patients and the adverse effects of their metabolites on albino rats and epithelial or fibroblasts cell lines - Mervat Morsy Abbas Ahmed El-Gendy; Huda Ahmed Alghamdi; Khaled G. Abdel-Wahhab; Nabila S. Hassan; Aya A. M. El-Bondkly; Mohammed Abdel-Wahab; Ayman A. Farghaly; Ahmed Mohamed Ahmed El-Bondkly (Infectious Agents and Cancer)
Abstract Background Cancer is a significant global health issue due to its high incidence and mortality rates. In recent years, the relationship between the human microbiota and cancer has garnered attention across various medical fields. This includes research into the microbial communities that influence cancer development, tumor-associated microorganisms, and the interactions between the microbiome and tumor, collectively referred to as the oncobiome. Methods The negative effects of secondary metabolites extracted from selected multidrug-resistant Gram-negative bacteria within the cancer microbiota were evaluated. These effects included carcinogenicity, mutagenicity, hepatotoxicity, nephrotoxicity, and sperm deformities observed in albino rats after one month of oral ingestion of these microbial extracts. Results Our findings in the present investigation revealed that among the bacterial community derived from the microbiota, Gram-negative bacteria accounted for 74.87% the total microbiota (146 out of 195) and their spectrum including Escherichia sp. (n = 36, 24.66%) followed by Acinetobacter sp. (n = 34, 23.29%), Stenotrophomonas sp. (n = 29, 19.86%), Pseudomonas sp. (n = 26, 17.81%) and Serratia sp. (n = 21, 14.38%), as the most prevalent pathogens. All isolates derived from the cancer microbiome exhibited multidrug resistance to a large number of conventional therapies. Out of them Serratia sp. Esraa 1, Stenotrophomonas sp. Esraa 2, Acinetobacter sp. Esraa 3, Escherichia sp. Esraa 4 and Pseudomonas sp. Esraa 5 strains showed multidrug resistant profile against all antibiotic classes under study including penicillins, cephalosporins, carbapenems, fluoroquinolones, β-lactamase inhibitors combinations, folate synthesis pathway inhibitors, phosphonic, aminoglycosides, polymyxins, tetracyclines, macrolides, and chloramphenicol antibiotics. The adverse effects of oral ingestion of their metabolites were evaluated in albino rats. They induced pronounced carcinogenesis along with severe raise in the inflammatory cytokines, hepatotoxicity, nephrotoxicity, mutagenicity along with sperm deformities in treated animals. Moreover, all metabolites showed marked cytotoxicity against human normal cell lines; human mammary epithelial (MCF10A), human lung fibroblasts (WI38) and human dermal fibroblasts (HDFs). Conclusion These bacterial strains isolated from the cancer microbiome may play significant roles in inducing cancer, inflammation, mutagenesis, hepatotoxicity, nephrotoxicity, and sperm abnormalities, along with histopathological changes in the treated animal groups by orally administrated metabolites in compared to the untreated group. Graphical Abstract